2015
DOI: 10.1007/s11032-015-0390-6
|View full text |Cite
|
Sign up to set email alerts
|

Predicting genetic variance in bi-parental breeding populations is more accurate when explicitly modeling the segregation of informative genomewide markers

Abstract: Robust predictions of genetic variances for important traits would facilitate greater genetic gains in plant breeding. Previous attempts to predict the genetic variance (r 2 G ) of traits in bi-parental breeding populations were inconsistent and context specific. The weakness of methods that consider the phenotypic distance, genetic distance, and relationship-based distance of pairs of parents, which we collectively term historical methods, stems from the fact that they do not explicitly model the segregation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 33 publications
4
45
0
Order By: Relevance
“…For example, in PHM81 ´ A588, the observed plant height was 134 cm, whereas the predicted plant height was 117 cm. The downward bias in the predicted V G for plant height (−59%) and ear height (−30%) in the current study was consistent with the downward bias of −28 to −60% found by Lian et al (2015) for V G for grain yield, moisture, and test weight but was larger than the minimal downward bias (−4%) reported by Tiede et al (2015). The correlation between the midparent phenotypic value and the observed mean of the population was 0.77 for ear height, 0.80 for silking Fig.…”
Section: Accurate Prediction Of the Population Mean But Not V Gsupporting
confidence: 88%
See 2 more Smart Citations
“…For example, in PHM81 ´ A588, the observed plant height was 134 cm, whereas the predicted plant height was 117 cm. The downward bias in the predicted V G for plant height (−59%) and ear height (−30%) in the current study was consistent with the downward bias of −28 to −60% found by Lian et al (2015) for V G for grain yield, moisture, and test weight but was larger than the minimal downward bias (−4%) reported by Tiede et al (2015). The correlation between the midparent phenotypic value and the observed mean of the population was 0.77 for ear height, 0.80 for silking Fig.…”
Section: Accurate Prediction Of the Population Mean But Not V Gsupporting
confidence: 88%
“…When compared with the results of previous studies (Lian et al, 2015;Tiede et al, 2015), our results suggested that virtual populations have erratic effectiveness for predicting V G . The results from this study do not support the use of genomewide marker effects, estimated from diverse inbreds, for predicting V G in maize biparental crosses.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Nevertheless, most previous studies used genome-wide molecular marker data, which lack specificity and accuracy. Tiede et al (2015) showed that segregating informative genome-wide markers could improve the accuracy of predicting genetic variance across 40 barley parents. Wegary et al (2013) suggested that the genetic distance calculated using selected markers associated with quantitative trait loci (QTL) may better predict heterosis.…”
Section: Discussionmentioning
confidence: 99%
“…The number of replications was informed from previously published uses of the PopVar package Tiede et al, 2015). The number of replications was informed from previously published uses of the PopVar package Tiede et al, 2015).…”
Section: Training Populationmentioning
confidence: 99%